MAPPING INTELLECTUAL TRENDS IN FIQH: The Written Legacy of Southern Tapanuli Scholars in the 20th Century - Ikbal, Muhammad; Asari, Hasan; Nasution, Wahyudin Nur (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2024)
Abstract: In 20th-century Southern Tapanuli, Islamic discourse prominently centered on fiqh (Islamic jurisprudence), reflecting historical circumstances and local challenges. Limited access to classical Middle Eastern texts prompted scholars to produce accessible, practical fiqh literature tailored to the community’s needs. This study analyzes their contributions by examining fiqh texts to identify thematic patterns and focus areas. The findings reveal that while fiqh education gained public prominence, the written works concentrated on foundational topics like purification (taharah), worship (ibadah), and almsgiving (zakat). These efforts highlight the pragmatic approach of Tabagsel scholars, ensuring that Islamic jurisprudence remained contextually relevant and responsive to societal needs.Keywords: Southern Tapanuli Scholars, Writing Tradition, FiqhStudies, Mandailing